2012
DOI: 10.1007/s00213-012-2676-2
|View full text |Cite
|
Sign up to set email alerts
|

Delayed preattentional functioning in early psychosis patients with cannabis use

Abstract: This study provides further evidence that MMN/P3a deficits are present during early psychosis and suggests that this biomarker may have utility in differentiating substance- from non-substance-related psychoses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 77 publications
1
14
0
5
Order By: Relevance
“…It is thought to represent basic auditory information processing, and sensory memory generated primarily in the superior temporal and prefrontal cortex (PFC), while being relatively independent of attention (161, 162). Deficits in MMN have been shown in patients with schizophrenia, early psychosis, and high-risk subjects (163, 164). While oral THC did not produce any acute changes in MMN amplitude (93), studies in chronic cannabis users have demonstrated decreased MMN amplitudes in the frequency deviance condition (154, 165167).…”
Section: Immediate Effects Of Cannabinoids: Experimental Evidencementioning
confidence: 99%
“…It is thought to represent basic auditory information processing, and sensory memory generated primarily in the superior temporal and prefrontal cortex (PFC), while being relatively independent of attention (161, 162). Deficits in MMN have been shown in patients with schizophrenia, early psychosis, and high-risk subjects (163, 164). While oral THC did not produce any acute changes in MMN amplitude (93), studies in chronic cannabis users have demonstrated decreased MMN amplitudes in the frequency deviance condition (154, 165167).…”
Section: Immediate Effects Of Cannabinoids: Experimental Evidencementioning
confidence: 99%
“…However, this pattern differs from the alterations observed in patients with schizophrenia who do not use cannabis [75]. Finally, results of Pesa et al [76] also suggest altered effects of cannabis in schizophrenia. While amplitudes of mismatch-related potentials were more pronounced in schizophrenic patients without cannabis use history as compared to patients with cannabis use, schizophrenic cannabis users showed longer latencies in some of these potentials.…”
Section: Discussionmentioning
confidence: 86%
“…This dimensional approach shifts the emphasis from making a specific diagnosis to determining the current level of cognitive or behavioral change in individual patients. Clinical and related neurobiological research then examines the extent to which common risk variables (for example, developmental delay, trait neurocognitive impairments, alcohol or other substance misuse) increase risk to measured behavioral or cognitive change, increase risk to markers of brain impairment (for example, poor neuropsychological function, excessive cortical thinning, disturbed neurophysiological markers) or increase risk to poor outcomes - independently of any specific relationship with classical ‘diagnostic’ entities [108,147,148]. …”
Section: Discussionmentioning
confidence: 99%